Evidence for a Na+/Ca2+ exchanger in neuroblastoma x glioma hybrid NG108-15 cells. - Hsu, L S (1995)
To determine whether NG108-15 cells contain a functional Na+/Ca2+ exchanger, we isotonically replaced extracellular Na+ with N-methyl-D-glucamine (NMG) and measured the effect on cytosolic Ca2+ concentration ([Ca2+]i) using the fluorescent Ca2+ indicator fura 2. Replacement with NMG alone had no effect on basal [Ca2+]i or the rise in [Ca2+]i evoked by 80 mM K+ or 10 microM bradykinin, but caused a larger [Ca2+]i increase when thapsigargin and carbonyl cyanide p-trifluoromethoxyphenylhydrazone (FCCP) were added to the cells; this enhanced [Ca2+]i increase could be reversed by adding Na+ back to the bathing buffer. The elevation in [Ca2+]i induced by thapsigargin and FCCP was inversely proportional to extracellular Na+ concentration. Furthermore, the exchanger operated in the reverse mode, as measured by either [Ca2+]i change or 45Ca2+ uptake. An 810 bp cDNA fragment of the exchanger was amplified by PCR; it differed by a single amino acid residue from the corresponding segment of the rat brain Na+/Ca2+ exchanger. These data suggest that a functioning Na+/Ca2+ exchanger exists in NG108-15 cells.